Craving al celular y estilos parentales en estudiantes de Psicología Clínica de la Universidad Nacional de Chimborazo. Riobamba, 2020 - Cruz Benítez, Lenin Damián (2020)
Worldwide, the cell phone takes on great importance in the lives of human beings, especially young people, who are attracted by the functionality and comfort that the device offers, reaching the point of exceeding the limit of need and becoming an urgency, affecting the relationship that the student has with the environment. The research focused on identifying the level of cell phone craving: intense and urgent hunger or desire to use the cell phone; and types of parenting styles in Clinical Psychology students. A non-experimental and cross- sectional study was carried out, with an intentional non-probabilistic sample of 364 students, made up of 72.53% women and 27.47% men. A sociodemographic survey was applied using the Mobile Phone Addiction Craving Scale (MPACS) and the Parental Styles and Perceived Inconsistency Scale (EPPIP), obtaining as predominant results: habitual user (36.26%) and authoritarian style (61.26%), without excluding the existence of a problem user (35.99%) and an overprotective type (28.30%). Based on the data obtained, the possible consequences could trigger a cell phone addiction; for this reason, psychoeducational strategies are proposed that focus on information, prevention, and reduction of cell phone craving and social skills development for the optimal growth of students with the environment.